Ecophysiology of cassava - Cock, James H.; Rosas, S.C. (International Center for Tropical Agriculture, 1975)
Cassava is a high-yielding crop, well adapted to areas of the tropics with low, uncertain rainfall and mean temperatures above 20 degrees Celsius.It has the ability to grow on very acid soils where few other crops will grow atall; however, highest yields are obtained under more fertile conditions. It willnot tolerate excessive moisture in the soil, which leads to root rots and lower yields. It responds well to the high solar radiation levels likely to be found in the drier tropical regions. Where long days are encountered, yields decline slightly. (AS)